IoRT-in-hand software. - Bravo-Arrabal, Juan; Cheng, Zhuoqi; Fernández-Lozano, Juan Jesús; Gómez-Ruiz, José Antonio; Schlette, Christian; Savarimuthu, Thisius Rajeeth; Mandow, Anthony; García-Cerezo, Alfonso José (Universidad de Málaga, 2025)
The integration of robotics and mobile networks (5G/6G) through the Internet of Robotic Things (IoRT) is revolutionizing telemedicine, enabling remote physician participation in scenarios where specialists are scarce, where there is a high risk to them, such as in conflicts or natural disasters, or where access to a medical facility is not possible. Nevertheless, touching a human safely with a robotic arm in non-engineered or even out-of-hospital environments presents substantial challenges. This article presents a novel IoRT approach for healthcare in or from remote areas, enabling interaction between a specialist’s hand and a robotic hand. We introduce the IoRT-in-hand: a smart, lightweight end-effector that extends the specialist’s hand, integrating a medical instrument, an RGB camera with servos, a force/torque sensor, and a mini-PC with Internet connectivity. Additionally, we propose an open-source Android app combining MQTT and ROS for real-time remote manipulation, alongside an Edge–Cloud architecture that links the physical robot with its Digital Twin (DT), enabling precise control and 3D visual feedback of the robot’s environment. A proof of concept is presented for the proposed tele-robotic system, using a 6-DOF manipulator with the IoRT-in-hand to perform an ultrasound scan. Teleoperation was conducted over 2300 km via a 5G NSA network on the operator side and a wired network in a laboratory on the robot side. Performance was assessed through human subject feedback, sensory data, and latency measurements, demonstrating the system’s potential for remote healthcare and emergency applications.
Keywords: Informática en la nube; Internet de los objetos; Robótica; Medicina - Material y equipo; Ingeniería biomédica; Simulación por ordenador; Android; Cloud robotics; Digital Twins; Medical instruments; Tele-operation